Evaluation of the late life disability instrument in the lifestyle interventions and independence for elders pilot (LIFE-P) study. - Hsu, Fang-Chi.; Rejeski, W Jack.; Ip, Edward H.; Katula, Jeff A.; Fielding, Roger.; Jette, Alan M.; Studenski, Stephanie A.; Blair, Steven N.; Miller, Michael E. (2016)
Background: The late life disability instrument (LLDI) was developed to assess limitations in instrumental and management roles using a small and restricted sample. In this paper we examine the measurement properties of the LLDI using data from the Lifestyle Interventions and Independence for Elders Pilot (LIFE-P) study.; Springer Open.